Desain komponen alat pengupas dan pengiris bawang putih - I Ketut Adhiarta Laksemana; Sri Nararia Anggita Damayanti; Farid Triawan (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
Garlic as a basic spice has never been separated from the processing food industry. The garlic processing process which includes stripping and slicing will take a lot of time if the processes are done manually on each clove of garlic. The study tried to help by designing and analyzing devices that could help users peel and slice garlic using a rotation mechanism. The design of this device is designed to peel 4 kg of garlic within 30 minutes by applying a force of 25 N. The device has a uniqueness, it can be disassembled and accompanied by additional features in the form of a slicer knife to make it easier to install and use the device. Based on the results of the analysis, the safety factor values at static and dynamic loads were obtained at 1.44 and 1.73 in the most critical parts. Therefore, it can be concluded that this product is safe and has an infinite age prediction. This study is expected to be a reference for the creation of better garlic peeling and slicer products.